On Autobiographical Writing: Georges Gusdorf and James Olney - Tornero, Angélica (2023)
The autobiographical writing studies have notably increased since the second half of the twentieth century. Theorists and critics from various disciplines, such as philosophy, literature, psychology, history, anthropology and education have given themselves the task of thinking about this type of writing. The amount and diversity of approaches have motivated us to take a closer look at the proposals in order to identify similarities and differences. The aim of this article is to examine, comparatively, Georges Gusdorf’s and James Olney’s explanations of the relationship between self-knowledge and the autobiographical writing. The starting point of these considerations is that although the similarities between the theories of these authors are more than the differences, it is possible to identify some variations, mainly in two aspects: questions of method and approaches into understanding the relationship between self-knowledge and time.